Prostate Specific Antigen (PSA) Levels and its Correlation to Prostatic Lesions - Londhe, Apurva Mangesh; Shah, Anita Bharat (Annals of Pathology and Laboratory Medicine, 2018)
Background: To correlate PSA levels with prostatic lesions and grade of Prostatic adenocarcinoma Methods: The study includes male patients with lower urinary tract complaints, advised to get their PSA levels and Transrectal ultrasound (TRUS) guided prostatic biopsy done. Study design was observational and retrospective. Universal sampling method has been used for selection, during study period May 2015 to September 2016. Ethical clearance has been obtained from Medical Ethical Committee of Saifee Hospital. We received 116 TRUS biopsies in the described time frame. The relevant data for these were collected from the hospital and departmental records. Results: Out of 116 cases, 57 cases were malignant and 59 cases were benign. Fifty-three (93%) of the malign1ant cases and 54 (91.5%) of the benign cases had PSA levels above 4 ng/ml. Thus, association of PSA level and type of lesion was found to be statistically insignificant (p >0.05). The mean PSA level was 19.67ng/ml in Grade 1 Prostatic adenocarcinoma, 10.84ng/ml in Grade 2 Prostatic adenocarcinoma, 21.07ng/ml in Grade 3 Prostatic adenocarcinoma, 39.06ng/ml in Grade 4 Prostatic adenocarcinoma and 399.26ng/ml in Grade 5 Prostatic adenocarcinoma. Thus, the mean PSA level increased as the grade increased but it was statistically not significant (p>0.05). Conclusion: Serum PSA level as tumor marker has limitations. Thus, histopathological examination is more specific for correct diagnosis in clinically suspicious cases.